Use of False Nearest Neighbours for Selecting Variables and Embedding Parameters for State Space Reconstruction. (9th March 2015) - Krakovská, Anna; Mezeiová, Kristína; Budáčová, Hana
Abstract : If data are generated by a system with a d -dimensional attractor, then Takens' theorem guarantees that reconstruction that is diffeomorphic to the original attractor can be built from the single time series in 2 d + 1 -dimensional phase space. However, under certain conditions, reconstruction is possible even in a space of smaller dimension. This topic is very important because the size of the reconstruction space relates to the effectiveness of the whole subsequent analysis. In this paper, the false nearest neighbour (FNN) methods are revisited to estimate the optimum embedding parameters and the most appropriate observables for state space reconstruction. A modification of the false nearest neighbour method is introduced. The findings contribute to evidence that the length of the embedding time window (TW) is more important than the reconstruction delay time and the embedding dimension (ED) separately. Moreover, if several time series of the same system are observed, the choice of the one that is used for the reconstruction could also be critical. The results are demonstrated on two chaotic benchmark systems.